Mengukur Pengaruh Faktor Makro Ekonomi Eksternal dan Internal Terhadap Cadangan Devisa Indonesia - Simanullang, Harjona; Dewanto, Fajar Wahyu; Waskito, Bima Aris; Reza, Muhamad; Musroni, Gebriel; Harefa, Yanuarman; Hukom, Alexandra (Jurnal Christian Humaniora, 2025)
Global economic uncertainty significantly affects countries with open economic systems. Foreign exchange reserves, as a fundamental indicator of a country's economic stability, must be maintained to ensure that economic activities remain stable amid global economic challenges. This study aims to identify and measure the influence of foreign debt, exports, and imports on Indonesia’s foreign exchange reserves, both simultaneously and partially. The data utilized are secondary data covering the period from 2009 to 2023. The analytical method employed is multiple linear regression analysis. The results of the analysis indicate that foreign debt, exports, and imports collectively have a significant effect on foreign exchange reserves. Partially, foreign debt has a positive and significant influence on foreign exchange reserves, while exports and imports both have a positive but not statistically significant influence. The coefficient of determination (R²) is 0.883411, which implies that 88.34% of the variation in Indonesia’s foreign exchange reserves can be explained by foreign debt, exports, and imports, whereas the remaining 11.66% is influenced by other variables not examined in this study.